Antibiotic Resistance in Escherichia coli Isolated from Feces of Bali Cattle With Reproductive Disorders - Kholik Kholik; Muhammad Munawaroh; Muhammad Rama Imam Saputra; Rahmawati Rahmawati; Pudji Srianto (UIN Sunan Gunung Djati Bandung, 2021)
Antimicrobial resistance (AMR) has become a global issue in animal, human and environmental health. The AMR profile of Escherichia coli reflects the use of antibiotics in production animals. The purpose of this study was to determine the antibiotic resistance of Escherichia coli bacteria isolated from the feces of female Bali cattle with reproductive disorders. Feces samples were taken purposively using a swab on 4 rectums from 7 Bali cattle with reproductive disorders in June 2021 in Lando Village, East Lombok Regency. Escherichia coli samples were isolated on Eosin Methylene Blue Agar media and identified by biochemical tests. An antibiotic resistance test against Escherichia coli was carried out by the disk diffusion method. The antibiotics used in the test were Penicillin G 10 U, Oxytetracycline 30 g, Gentamicin 10 g, and Tetracycline 30 g, and Cefotaxime 30 g. The results of planting on Eosin Methylene Blue Agar media obtained 4 Escherichia coli which were successfully isolated from 4 samples of Bali cattle feces. Data on the level of Escherichia coli susceptibility level to various antibiotics were analyzed using the chi-square test. The results of the susceptibility test to antibiotics showed that 4 samples of Escherichia coli (100%) were resistant to Penicillin G, (25%) were resistant to Oxytetracycline, (25%) were resistant to Cefotaxime, and (100%) samples of Escherichia coli were sensitive to Gentamicin and Tetracycline. The chi-square test on the level of Escherichia coli susceptibility to various antibiotics was significant with p˂ 0.05 (p-value = 0.012). The results of this study have shown that Escherichia coli from Bali cattle feces experience multidrug resistance which later on might have an impact on human health and the environment.